IDENTIFIKASI SERANGGA ADAPTIF DI KAWASAN HUTAN WISATA MANGROVE SEKOTONG, LOMBOK BARAT - Sri Anjar Wani; Munawir Sazali (Bioscientiae, 2026)
Coastal areas are transitional areas between terrestrial and marine ecosystems. Mangrove forests are tropical natural resources that have multiple benefits, both in terms of social, economic, and ecological aspects. The purpose of this study was to identify adaptive insects in the Sekotong mangrove forest tourism area. This research method uses a descriptive explorative method to identify types of adaptive insects along the tourist route in the Sekotong mangrove forest tourism area. Several types of adaptive insects that live along the Sekotong Mangrove Forest tourism route were found to be 7 species, namely Menemerus bivittatus, Solenopsis invicta, Lepidoptera, Euploea midamus, Simuliidae, Monomorium carbonarium and Xylocopa virginica. The results of this study were that the Solenopsis invicta species (fire ants) was the most dominant species, followed by Monomorium carbonarium, as found in the Shannon-Wiener diversity index value (H’<1) for all observation plots. The low diversity of insects in the Sekotong mangrove area can be caused by several ecological factors such as mangrove vegetation structure and environmental pressure.